Synthesis and structural characterization of binuclear palladium(II) complexes of salicylaldimine dithiosemicarbazones - Stringer, Tameryn; Chellan, Prinessa; Therrien, Bruno; Shunmoogam-Gounden, Nelusha; Hendricks, Denver T.; Smith, Gregory S. (My University, 2009)
Binuclear Pd(II) salicylaldiminato dithiosemicarbazone complexes were synthesized and characterized. The Pd complexes were obtained by the reaction of various ethylene- and phenylene-bridged dithiosemicarbazones with Pd(PPh3)2Cl2. The free salicylaldimine ligands and their Pd complexes were characterized by NMR and IR spectroscopies, ESI-mass spectrometry, elemental analyses and for two representative complexes also by x-ray diffraction. In both metal complexes, the solid-state structures show the two Pd centers to be coordinated in a slightly distorted square-planar geometry, which gives rise in each case to five- and six-membered chelate rings. The salicylaldimine thiosemicarbazone ligands coordinate to Pd in a tridentate manner, through the phenolic O, imine N and thiolate S atoms. [on SciFinder(R)]
Keywords: palladium salicylaldimine dithiosemicarbazone binuclear complex prepn crystal structure